A CORRELATION BETWEEN THYROID STIMULATING HORMONE AND BODY MASS INDEX IN WOMEN WITH SUBCLINICAL HYPOTHYROIDISM IN NCR - Gupta, Gaurav; Itagappa, M; Kumar, Pradeep; Sharma, Rachna; Sharma, Preeti (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Weight gain is a characteristic feature of hypothyroidism. People with subclinical hypothyroidism (SCH) are also characterized by the same is still unclear. Methods: Height and weight were calculated of SCH women as well as normal healthy adult women. Body mass index (BMI) was calculated as per WHO guidelines. The thyroid stimulating hormone (TSH), FT4, and T3 were measured by Enzyme-Linked Immunosorbent Assay technique. Results: Thyroid profile (TSH and T3) was significantly (<0.05) different between subclinical hypothyroidism women and normal women. Women with subclinical hypothyroidism were having higher TSH (13.01±4.41 vs. 2.61±0.79) compared with normal healthy control group along with different T3 (0.94±0.17±1.09±0.26) between the groups. The serum concentration of FT4 was not significant between the groups. The body mass index, higher (28.81±3.47 vs. 22.62±1.57) in subclinical hypothyroidism women, was highly significant (<0.001). BMI was positively correlated with TSH in SCH (0.36) group as well as normal control (0.50) group. The correlation was significant (<0.05) in both the groups. Conclusion: People with subclinical hypothyroidism were characterized by increased weight gain. Thereby it is concluded that Thyroid Stimulating Hormone affects the Body Mass Index in SCH women. Our result suggests that estimation of thyroid profile, also within the normal range, could be one of several factors acting in concert to determine body weight. However, this parallel increase in BMI due to weight gain along with increase in TSH may further leads to overt hypothyroidism if left untreated. Obesity itself could produce various metabolic disorders in coming future. Keywords: Subclinical hypothyroidism, Body mass index, Thyroid stimulating hormone.